2020
DOI: 10.1111/tmi.13416
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a water, sanitation and hygiene program on handwashing with soap among household members of diarrhoea patients in healthcare facilities in Bangladesh: a cluster‐randomised controlled trial of the CHoBI7 mobile health program

Abstract: Objective The Cholera‐Hospital‐Based‐Intervention‐for‐7‐days (CHoBI7) is a water treatment and handwashing with soap intervention for diarrhoea patients and their household members which is initially delivered in a healthcare facility setting. This study evaluated the effectiveness of CHoBI7 program delivery in increasing handwashing with soap in a healthcare facility setting among diarrhoea patients and their household members. Methods A randomised controlled trial of the CHoBI7 program was conducted among 40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…29,37,38 However, evidence is limited about successful integration of mHealth applications and their effectiveness for environmental health interventions-especially in urban communities where this work is critical. [39][40][41][42] Potential examples of mHealth deployment [43][44][45] to meet urban sanitation challenges are highlighted in Figure 1 and include interactive messages, uploading and geotagging of pictures to report and record the location of environmental issues, and user-provider feedback loops. 26 In many settings, evidence shows that mHealth approaches can be highly cost-effective and scalable.…”
mentioning
confidence: 99%
“…29,37,38 However, evidence is limited about successful integration of mHealth applications and their effectiveness for environmental health interventions-especially in urban communities where this work is critical. [39][40][41][42] Potential examples of mHealth deployment [43][44][45] to meet urban sanitation challenges are highlighted in Figure 1 and include interactive messages, uploading and geotagging of pictures to report and record the location of environmental issues, and user-provider feedback loops. 26 In many settings, evidence shows that mHealth approaches can be highly cost-effective and scalable.…”
mentioning
confidence: 99%
“…44 A second cohort study in this population assessed the association between soil-and object-to-mouth contacts and diarrhea prevalence for children under 5 years of age, and found that the odds of having a diarrhea episode in the subsequent month were significantly higher for children with caregiver reports of mouthing feces within the past week. 16 Additional publications document the CHoBI7 mHealth program effect on handwashing with soap while in the hospital, 45 diarrheal disease knowledge, 46 process evaluation for CHoBI7 mobile health program delivery, 47 and recent formative research to develop a CHoBI7 Baby WASH mHealth program targeting safe child feces disposal, improved food hygiene, and safe child mouthing practices. 48 This prospective cohort study, also nested within the recent CHoBI7 mHealth program RCT, adds to this body of literature by investigating the environmental and individual-level risk factors for diarrheal disease among children under 5 years of age residing in slum areas of Dhaka, Bangladesh.…”
mentioning
confidence: 99%
“…There is a concomitant occurrence between wasting, stunting, and diarrhea. Dehydrating diarrhea is reported more frequently (69%) among children with severe wasting and severe stunting than among children with severe wasting (55%) or severe stunting (43%) 28 . A recent study in Odisha, India found that around 24% of children suffered from wasting during the monsoon season as compared to only 16% in the winter season 24 .…”
Section: Discussionmentioning
confidence: 99%